SKALA KEBAHAGIAAN REMAJA MUSLIM - Ratih Kumaya Jati; Amida Cindy Septiana; Adhitya Akbar Sultoni; Deina Chellyn Wisna A; Izzati Laila Markhamah (Fakultas Psikologi Universitas Wijaya Putra, 2022)
This study was designed to create a psychological measuring instrument with a variable of happiness in Muslim adolescents named the “Muslim Youth Happiness Scale” (MYHS). Questionnaires were given to 114 participants who met the characteristics of adolescent boys or girls aged between 12-24 years. The research method used is the construction method of psychological measuring instruments (psychometry). The item scale is built by 5 item makers by creating each scale. The initial points are then recapitulated and internal constructors are eliminated with a total of 14 people consisting of psychology students, psychology study program lecturers, and psychology. The results of this study are a psychological scale consisting of three aspects with 18 items, where each aspect contains 9 items with 3 items per indicator. This aspect consists of Past Positive Emotions, Present Positive Emotions, and Future Positive Emotions. Aiken's V and Cronbach's Alpha scores on the scale are 0.68-0.93 and 0.838, respectively. This adolescent happiness scale shows the reliability and validity of the content which is quite good for assessing happiness in Muslim adolescents. The abbreviated version of the Muslim adolescent happiness scale developed and validated in this study can be used to measure the happiness of Muslim adolescents in the community and other research areas.